A WALL JET ELECTRODE FOR INSITU ELECTROCHEMICAL ESR - Compton, R; Greaves, C; Waller, A (1990)
A novel cell suitable for in-situ electrochemical ESR is described. This is based upon a wall-jet design and is shown to function as a satisfactory hydrodynamic electrode. The cell can be located within an ESR cavity without appreciable perturbation of the sensitivity of the ESR technique allowing the measurement of high quality ESR spectra of electrogenerated radicals. © 1990.